THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK MOTIVATION, AND ORGANIZATIONAL COMMITMENT TO THE PERFORMANCE OF PRINCIPALS - Puji Syamsuri (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The purpose of this study was to determine the influence of organizational culture, work motivation, and organizational commitment to the performance of principals of elementary school in Samarinda. The results of the study findings that: (1) Organizational cultures have directly positive effect to the performance of principals, (2) Work motivation have directly positive effect to the performance of principals, (3) Organizational commitment have directly positive effect to the performance of principals, (4) Organizational culture have directly positive effect to the organizational commitment, (5) Work motivation have directly positive effect to the organizational commitment. This research was carried out in the environment of Samarinda Government that involving 60 principals of elementary school in Samarinda as the study samples. The determination of study samples was done by using random sampling. The data collection using instrument with a Likert scale of measurement consist of 5 answer options and the data analysis using path analysis technique. Based on the study, organizational culture, work motivation, and organizational commitment have directly positive effect to the performance of principals. Therefore the variables of the study are recommended to the Government of Samarinda to increase the performance of elementary school in Samarinda. Keywords: Organizational Culture, Work Motivation, Organizational Commitment and Performance of Principals, Education Office of Samarinda City.